Faktor Pernikahan Dini Dan Dampaknya Terhadap Kesejahteraan Remaja Di Kecamatan Tersono Kabupaten Batang - Amalinda, Dayana; Maharani, Sania; Hami, Widodo (LPPM UNU BLITAR, 2024)
he phenomenon of early marriage is a subject that is not only interesting, but also urgent to be understood in more depth. Apart from various policies and programs that have been implemented to reduce the rate of early marriage. In relation to psychological well-being, this phenomenon can make a significant contribution to adolescents' experiences in various aspects of their lives. Early marriage is a phenomenon that urgently needs to be studied in depth in the context of adolescent psychological development, especially in the Tersono sub-district. In the areas we studied, there was an increase in cases of marriage at an age where they were not yet fully mature physically, emotionally and socially. This condition raises various critical questions regarding its impact on the psychological well-being of teenagers affected by cases of early marriage. This type of research is field research and the author focuses more on qualitative research methods in carrying out this analysis. Factors that influence early marriage include economic factors, low awareness of the importance of education, cultural factors, factors from the individual himself, and from social media. Early marriage has a negative impact on adolescent well-being, reproductive health, employment opportunities and mental health.